Relationship between Learning Style and Motivation on Student Learning Outcomes at MAN Insan Cendikia Palu - Firmansyah, Moh.; Hasdin, Hasdin; Jamaludin, Jamaludin (Journal of Education Method and Learning Strategy, 2024)
The aim of this research is to analyze the significant relationship between learning style and motivation on student learning outcomes in class XII Civics subjects at MAN Insan Cendikia Palu. This research is quantitative research using descriptive analysis. Data collection was carried out by conducting observations, questionnaires and documentation. The research subjects were class XII students at MAN Insan Cendikia Palu. The sample in this research consisted of 45 students. Data collection methods use documentation and questionnaires. The instruments used in this research have met the criteria for validity and reliability. The results of the research show that there is a significant positive relationship where the r count is 0.805, so the relationship between learning style (visual) and learning outcomes in Civics subjects in class XII MAN Insan Cendikia Palu is in the very high category. There is a significant positive relationship between the learning style (auditory) and the learning outcomes of PPKn subjects for class in the high category. Based on the r value interpretation table where r is 0.791, the relationship between learning style (kinesthetic) and learning outcomes in Civics subjects in class XII MAN Insan Cendikia Palu is in the high category. There is a positive and significant relationship between learning motivation and the learning outcomes of Civics subjects in class XII MAN Insan Cendikia Palu with a significance value of 0.000. There is a positive and significant relationship between learning style and learning motivation together with the learning outcomes of Civics subjects in class .